Tecnologia para produção de extrato aquoso de amendoim - Pretti, Taciana [UNESP]; Carvalho, Maria Regina Barbieri de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Aiming to increase nutritional and technological utilization of the peanut, this research was carried out to produce an aqueous extract, with variations in processing. The procedure to obtain the extract consisted of heating the beans in 0.5% of sodium bicarbonate solution until boiling (1:4w/v), draining, washing, disintegrating and fi ltrating. It was evaluated two temperatures (75ºC and 97ºC) and two amounts of grain: water (1:5 and 1:8w/v) in disintegration of the grains. Water at 75ºC produced extract with low content of lipids (5.87%), and high content of carbohydrates (2.31%). The extracts components were signifi cantly diluted with the water proportion 1:8W/v, which permitted the highest yield (1:6.92kg), better total solids and protein extraction and lower loss of solids in the waste. The heating of grains at 97ºC provided protein with the highest digestibility (80.6%). We conclude that a balance is needed between the proportions of grains and water as well as an appropriate temperature for a perfect preparation of the aqueous extract of peanuts.

Visando ampliar o aproveitamento nutricional e tecnológico do amendoim, realizou-se este trabalho com o objetivo de elaborar extrato aquoso com diferentes processamentos. O procedimento para obtenção do extrato consistiu no aquecimento dos grãos em solução de bicarbonato de sódio a 0,5% (1:4, p/v) até ebulição, com posterior drenagem, lavagem, desintegração e fi ltração. Foram avaliadas duas temperaturas (75ºC e 97ºC) e duas proporções de grão:água (1:5 e 1:8p/v) para a desintegração dos grãos. Água a 75ºC produziu extrato com o menor conteúdo de lipídeos (5,87%) e maior de carboidratos (2,31%). Os componentes dos extratos foram signifi cativamente diluídos com a maior proporção de água (1:8p/v), que permitiu o maior rendimento (1:6,92kg), a maior extração de sólidos totais e proteína e a menor perda de sólidos no resíduo. O aquecimento dos grãos a 97ºC propiciou proteína com maior digestibilidade (80,6%). Conclui-se que é necessá- rio um equilíbrio entre as proporções de grãos e água, bem como uma temperatura adequada, para uma perfeita elaboração do extrato aquoso de amendoim.
Technology for production of aqueous extract of peanut
Keywords: Arachis hypogaea; Digestibility; Grain; Water; Yield; Arachis hypogaea; Digestibilidade; Rendimento; Proporção; Sólido; Líquido